Asia Pacific Summits : how China, US and ASEAN can collaborate - Zha, Daojiong (2012)
The annual series of summits in the Asia Pacific has begun. Questions abound about the efficacy of these highprofile meetings. It’s time that China, the United States and Southeast Asia think about collaborating on non-traditional security projects.